Analisis Pembiayaan Keuangan Perbankan : Tinjauan Mendalam Terhadap Akad Mudharabah - Raihan Rahmatullah; Mutafikatul Khoiriyah; Silvia Kurnia Illahi; Renny Oktafia (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
This study uses a qualitative approach with the method of literature research to deepen the topic of financial financing on the Mudbah contract, adaptation and management of the Murabahah contract by Islamic banking, as well as the benefits and challenges faced by banks and customers in Mudharabah. Through an extensive literature review of various trusted sources, including books, journals, and research papers, this study aims to provide a comprehensive understanding of the subject matter.